A Theory of Collective Bargaining - Hameed, Syed (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1970)
The author brings out the inadequacies of the present theoretical models in explaining collective bargaining and provides the constructs of a more complete and integrated body of theory. He also notes the importance of using functional terms in a theoretical model of this kind.